Government Buildings, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Cannings and Co. Ltd., Trinidad, 2010)
Early exterior view of the government building popularly known as the "Red House" where the Trinidad and Tobago Parliament meets. It is bounded by Knox Street on the north, St. Vincent Street on the West, Hart Street on the South and Abercromby Street on the east. A horse and carriage are proceeding along Abercromby Street.
Colour: Red, White, Green, Black, Blue; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Architecture--Trinidad and Tobago; Red House, The